Kísérlet a Délvidék feltámasztására : a Duna-Körös-Maros-Tisza Eurorégió megalakulása és első eredményei (1997-2001) - Gulyás, László; Nagy, Imre (Közép-Európai Közlemények, 2011)
Hungarian regionalist and geographical literature agrees on the fact that at the turn of the 19–20th century economic regions started to form in Hungary. Although there are debates about the number, area and centers of these regions, scientist all agree that these regions could have become real regions if undisturbed in their development. But the wars and treaties of the 20th century did not allowed an undieturbed development, most of these regions were divided several times. One of the regions were Délvidék, divided between Romania, Yugoslavia and Hungary by the treaty of Trianon in 1920. At the end of the 20th century there was another wave of forming euro-regions in Middle Europe, when the Danube–Kris–Mures–Tisa Euroregion has been born. The paper presents the birth of this region and its first achievements.